Drug-food interaction most important and highly underappreciated aspect of therapeutics in a health care centre: A prospective observational study - ARPAN DUTTA ROY,; ANKITA BISWAS,; BRATATI DHARA,; BANALATA DAS,; VISHNU. R. NAIR, (International Journal of Pharma and Bio Sciences, 2019)
Drug-food interactions can lead to varied drug responses, culminating in altered efficacy status. A prospective observational study was conducted for a period of six months to assess different types of drug-food interactions of Kolkata, East India. Around 600 patients were enrolled into the study, and their prescription and diet instructions were reviewed throughout the six-month time period. The study was conducted, which included daily observation of prescriptions, medications provided and the diet instructions of patients. Diet information of patients was collected from dietetics department, kitchen and from allocated nursing staffs. Datas were collected using data collection forms, and entered into electronic database for further analysis of different types of interactions, along with their severity. Since many diseases are chronic in nature, requiring long-term pharmacotherapy, knowledge regarding adverse effects of drugs, along with interactions of the same with dietary products, is absolutely essential. Since food-drug interactions can interfere with efficacy and safety of drug therapy, as well as producing detrimental effects on nutritional status of patients, a standard guideline of drug-food interaction should be introduced in the hospital. Proper counselling of patients by doctors, dieticians and clinical pharmacists regarding food intake and modifications required while taking certain drugs can help in attenuating clinically significant food-drug interactions and their detrimental aftermaths.